-1=x-4/6

Simple and best practice solution for -1=x-4/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=x-4/6 equation:



-1=x-4/6
We move all terms to the left:
-1-(x-4/6)=0
We add all the numbers together, and all the variables
-(+x-4/6)-1=0
We get rid of parentheses
-x-1+4/6=0
We multiply all the terms by the denominator
-x*6+4-1*6=0
We add all the numbers together, and all the variables
-x*6-2=0
Wy multiply elements
-6x-2=0
We move all terms containing x to the left, all other terms to the right
-6x=2
x=2/-6
x=-1/3

See similar equations:

| x/8+8=6 | | 21=t-9 | | -9-8b=55 | | -9s=-7s-6 | | n=-7+16 | | 5-x=12. | | 9p^2=6=42 | | -8-3j=-4j | | -7f=9-8f | | 6x+8x=2x | | 4t+4=19 | | 25x-44=406 | | 8x–2–5x+7=1x+0 | | 800=x+(x*0.2) | | 6=2/7(2x+28) | | -4(a-2)+2a-8=-12 | | 47x-25=500 | | -10-7=5m-4(3+m) | | 5=8−3w | | 25x-44=11 | | 3-2y=4y-11 | | 8p+5p=35-9 | | 8x^2+70X-18=7 | | 9p+6p=47-2 | | 44=4x-3x | | 7(y-2)-6y=10 | | 9+x=67 | | 12x+69x=12 | | 1x+(-1)=1x+1 | | 112x-140=14(8x-10) | | 11x+76=11x+70 | | x-14-6=84 |

Equations solver categories